AI and Digital Literacy in Language Education: A Systematic Review on Critical Thinking Development - Iskandar, Zelvi; Yulanda, Nurul Izhan Pepridel; Dubey, Shibani Basu; Apriani, Eka (Journal of Language and Literature Studies, 2025)
Rapid advances in artificial intelligence (AI) have reshaped language education and raised new questions about how AI interacts with digital literacy and critical thinking development. This study presents a Systematic Literature Review (SLR) following PRISMA 2020, examining Scopus-indexed articles published between 2015–2025. A total of 58 records were identified, 44 were screened, and 14 full-text studies were included for qualitative thematic synthesis. The findings reveal that AI literacy, digital literacy, and critical thinking operate as an interdependent cognitive ecosystem in language learning: AI functions as a cognitive mediator that can stimulate analytical reasoning; digital literacy equips learners to navigate and evaluate multimodal information; and critical thinking serves as an epistemic and ethical filter for responsible meaning-making. Effective pedagogical strategies identified include AI-supported inquiry, reflective scaffolding, and project-based digital literacy tasks, with teachers and virtual communities of practice serving as ethical mediators and collaborative support structures. Key challenges—cognitive offloading, algorithmic bias, and digital divides—pose risks to learner autonomy and equitable learning outcomes. To bridge these issues, this review proposes the AI-Enhanced Critical Literacy Pedagogy (AICLP) model, offering an integrative framework that connects cognitive, reflective, and ethical dimensions for strengthening critical thinking in AI-mediated language education. The model provides theoretical grounding and practical guidance for curriculum design, teacher development, and education policy in the digital era.